Anterior insular cortex activity to emotional salience of voices in a passive oddball paradigm - Chen, Chenyi; Lee, Yu-Hsuan; Cheng, Yawei (Frontiers in Human Neuroscience, 2014)
The human voice, which has a pivotal role in communication, is processed in specialized brain regions. Although a general consensus holds that the anterior insular cortex (AIC) plays a critical role in negative emotional experience, previous studies have not observed AIC activation in response to hearing disgust in voices. We used magnetoencephalography to measure the magnetic counterparts of mismatch negativity (MMNm) and P3a (P3am) in healthy adults while the emotionally meaningless syllables dada, spoken as neutral, happy, or disgusted prosodies, along with acoustically matched simple and complex tones, were presented in a passive oddball paradigm. The results revealed that disgusted relative to happy syllables elicited stronger MMNm-related cortical activities in the right AIC and precentral gyrus along with the left posterior insular cortex, supramarginal cortex, transverse temporal cortex, and upper bank of superior temporal cortex. The AIC activity specific to disgusted syllables (corrected p < .05) was associated with the hit rate of the emotional categorization task. These findings may clarify the neural correlates of emotional MMNm and lend support to the role of AIC in the processing of emotional salience already at the preattentive level.